Back to the wilds: Tapping evolutionary adaptations for resilient crops through systematic hybridization with crop wild relatives2. Issue 10 (1st October 2014) - Warschefsky, Emily; Penmetsa, R. Varma; Cook, Douglas R.; von Wettberg, Eric J. B.
Abstract : The genetic diversity of our crop plants has been substantially reduced during the process of domestication and breeding. This reduction in diversity necessarily constrains our ability to expand a crop's range of cultivation into environments that are more extreme than those in which it was domesticated, including into "sustainable" agricultural systems with reduced inputs of pesticides, water, and fertilizers. Conversely, the wild progenitors of crop plants typically possess high levels of genetic diversity, which underlie an expanded (relative to domesticates) range of adaptive traits that may be of agricultural relevance, including resistance to pests and pathogens, tolerance to abiotic extremes, and reduced dependence on inputs. Despite their clear potential for crop improvement, wild relatives have rarely been used systematically for crop improvement, and in no cases, have full sets of wild diversity been introgressed into a crop. Instead, most breeding efforts have focused on specific traits and dealt with wild species in a limited and typically ad hoc manner. Although expedient, this approach misses the opportunity to test a large suite of traits and deploy the full potential of crop wild relatives in breeding for the looming challenges of the 21st century. Here we review examples of hybridization in several species, both intentionally produced and naturally occurring, to illustrate the gains that are possible. We start with naturally occurring hybrids, and then examine a range of examples of hybridization in agricultural settings.